2016
DOI: 10.9734/jgeesi/2016/27287
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of El -Niño Southern Oscillation (ENSO) Phenomenon on Rainfall Variation in Kaduna Metropolis, Nigeria

Abstract: Aim and Objectives:The aim of this study is to investigate the influence of El -Niño Southern Oscillation (ENSO) on rainfall variation in Kaduna metropolis from the year 1973-2013. Study Design: Precipitation data was sourced from NIMET (Kaduna airport) while Sea Surface Temperature Anomaly and Southern Oscillation Index data was acquired from the National Oceanographic Atmospheric Administration (NOAA) climate prediction centre's website. Methodology: These were analyzed to determine the extent of variation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…On the other hand, [20], [21], [22] have all shown that NDVI is closely related to biophysical parameters such as photosynthetical active radiation, leaf area index, biomass vegetation etc. and [12] also confirmed that seasonal and sub-seasonal signals of vegetation can be detected from NDVI data and consequently climatic variability related to El -Niño Southern Oscillations (ENSO). According to [23] desertification is one of the most serious problems facing northern Nigeria with dire economic consequences for the nation.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…On the other hand, [20], [21], [22] have all shown that NDVI is closely related to biophysical parameters such as photosynthetical active radiation, leaf area index, biomass vegetation etc. and [12] also confirmed that seasonal and sub-seasonal signals of vegetation can be detected from NDVI data and consequently climatic variability related to El -Niño Southern Oscillations (ENSO). According to [23] desertification is one of the most serious problems facing northern Nigeria with dire economic consequences for the nation.…”
Section: Introductionsupporting
confidence: 72%
“…VCI values of 35% and under indicate drought although long-term changes in NDVI data have been evaluated in several studies with some inconclusive results. This according to [12] is as a result of differences in the tools used, data processing techniques and the length and time of the analysed time series. Table 7 thus, shows the vegetation condition index across Kaduna state.…”
Section: Coefficient Of Variation Median Centeredmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the link between rainfall patterns and ENSO in Nigeria in an attempt to establish whether there is any direct relationship between rainfall variability, extreme weather event such as drought and flood as well as other rainfall characteristics such as the onset and cessation of rainfall, length of growing season, amount of rainfall to mention a few. While some of these studies revealed no direct relationship between rainfall patterns and ENSO since it brings both rainfall surplus and deficit (Shehu,et al, 2016 andNnawuike, et al, 2016) others, indicate that ENSO has direct influence on the rainfall parameters in Nigeria (Ati, et al, 2010and Benard, 2000cited in Shehu, et al, 2016.…”
Section: Introductionmentioning
confidence: 99%